The prospects of creating nutritious products based on raw materials of plant origin (Eurasian Journal of Ecology, 2016)
This article exzamines nutrient medium and the raw material used for its preparation, including the described types of raw material of plant origin used in the biotechnological production.
Keywords: culture media; plant material; microorganisms; molasses